Particle physics : an introduction - Purdy, Robert (Lecturer in Physics) (Mercury Learning and Information, 2018)
This book is designed as a brief introduction to the fundamental particles that make up the matter in our universe. Numerous examples, figures, and simple explanations enable general readers and physics students to understand complex concepts related to the universe. Selected topics include atoms, quarks, accelerators, detectors, colliders, string theory, and more.
Keywords: Particles (Nuclear physics); elektronické knihy; electronic books